2019
DOI: 10.1002/lom3.10328
|View full text |Cite
|
Sign up to set email alerts
|

Biased measurements by stationary turbidity‐fluorescence instruments due to phototactic zooplankton behavior

Abstract: Submersible fluorescence and turbidity sensors are widely used in studies of oceans and lakes. To reduce the instrument size, an overlapping interrogation volume is commonly used for the two sensors. Fluorescence sensors emit blue light for excitation and measure the red light emitted by excited chlorophyll pigments. However, during the night, many phototactic zooplankters are attracted to the blue light. If the instrument is fixed in place (e.g., on a mooring), the aggregation of the attracted animals may bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…Using manipulative lab experimentation, similar swarms observed within the optical path of the fluorometer were tightly correlated with increased sensor bias. Both laboratory and field results align with the findings of Tanaka et al (2019), confirming the potential for FIZ bias as a problem in both marine and freshwater environments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Using manipulative lab experimentation, similar swarms observed within the optical path of the fluorometer were tightly correlated with increased sensor bias. Both laboratory and field results align with the findings of Tanaka et al (2019), confirming the potential for FIZ bias as a problem in both marine and freshwater environments.…”
Section: Discussionsupporting
confidence: 87%
“…While phototaxis may be a primary behavior driving FIZ bias, this response should not be taken out of the broader context of DVM and its relation to zooplankton grazing. Tanaka et al (2019) linked sensor bias with the fluorescence of ingested phytoplankton, and given previous work using fluorometers to detect fluorescence through the carapace of zooplankton (Karaköylü et al 2009), it can be assumed that the quality, quantity, and residency times of florescent compounds within the digestive tract of a zooplankton will influence the magnitude of FIZ bias. Gut residency times of the freshwater cladoceran Daphina pulicaria were found to range from 4 to 106 min (Murtaugh 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that there were several larger than expected decreases in fluorescence between night and day profiles that are unexplained by the features of the model. These larger changes are potentially due to movement in the DCM (perhaps due to internal seiche waves), changes in sensor calibration, or even optical path interference by zooplankton (Tanaka et al 2019; V. W. Moriarty et al pers. comm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that periods of spikes in optical profiles were associated with the periodic interaction of zooplankton with transmissometers (Bishop et al, 1999;Bishop & Wood, 2008). Zooplankton are also associated with backscattering "spikes", defined here as a sharp and large increase in the optical signal (similar to Briggs et al, 2011, and detailed in the supporting information), in measurements collected by sensors mounted on a surface underway system and on an underwater stationary observatory (Burt & Tortell, 2018;Tanaka et al, 2019). These observations suggest that the presence of a subset of mesopelagic organisms could be estimated using BGC-Argo optical profiles and that the presence of spikes in optical instruments should not be interpreted a priori as an indication of sinking particles.…”
Section: Introductionmentioning
confidence: 92%